DIAGNOSIS AND SURGICAL TREATMENT OF LEFT SIDE CHRONIC OCCLUSIVE RENAL AND ILIAC VEINS IN ADOLESCENT - I.N. Nurmeev; L.F. Rashitov (Вопросы современной педиатрии)
Embarrassment of left renal and common iliac veins is a congenital abnormality of veins. In single patients this abnormality can lead to regional venous hypertension. Diagnosis and treatment of this state in pediatric practice are not developed. Adolescent patients (n = 61) with embarrassment of left iliac or/and renal veins were treated in 2002–2006 years. The main signs of embarrassment were: varicocele, dilatation of subcutaneous veins and edema of left leg, proteinuria, microhematuria, pain in left renal area. Ultrasonic doppler and renophlebography with phlebotonometry were used in all patients. Indication to different types of surgical procedures, depending on angiographic data and intensity of blood supply disturbance were developed. The intensity of blood supply was measured with pressure gradient. 61 surgical procedures were carried out with the control of intra operative phlebotonometry. Decrease of blood pressure gradient in left renal and iliac veins was chosen as an efficacy criterion. All treated patients had a significant decrease of blood pressure gradient in left renal and iliac veins.Key words: adolescents, venous hypertension, renal veiniliac vein, iliac artery, embarrassment syndrome.